Regulation of Interfacial Polarization and Local Electric Field Strength Achieved Highly Energy Storage Performance in Polyetherimide Nanocomposites at Elevated Temperature via 2D Hybrid Structure. Issue 28 (4th September 2022) - Ding, Xiangping; Pan, Zhongbin; Zhang, Yong; Shi, Songhan; Cheng, Yu; Chen, Hanxi; Li, Zhicheng; Fan, Xu; Liu, Jinjun; Yu, Jinhong; Zhai, Jiwei
Abstract: Dielectric materials with excellent high‐temperature energy storage performances are urgently demanded in advanced electronic market. However, the sharply reduced energy storage capabilities caused by conduction loss impede the applications of polymer‐based nanocomposites at harsh environments. In this work, the 2D hybrid structure fillers of boron nitride nanosheets‐titanium dioxide (BNNSs‐TiO2 ), where TiO2 nanoparticles tightly wrap around the 2D BNNSs, are fused with polyetherimide (PEI) forming polymer nanocomposite films. The finite element simulation and experiment results indicate that the hybrid structure 2D BNNSs‐TiO2 can effectively regulate local electric field strength and interfacial polarization, facilitating the enhancement in energy storage properties. Accordingly, the composite film delivers a superior discharged energy density (≈4 J cm −3 ) and charging/discharging efficiency (≈90%) at 150 °C, better than recently discussed high‐temperature pristine polymer and their composite films. This contribution offers a feasible idea to explore reliable dielectric capacitors at high temperature. Abstract : 2D Hybrid structure polymer nanocomposites exhibit remarkable capacitive energy storage performance, including high energy density, great charge–discharge efficiency, and excellent dielectric stability at elevated temperatures. This work enables the rational design of high‐energy‐density dielectric polymer composites with a wide working temperature range.